Accessing antiretroviral therapy for children: Caregivers' voices - Margaret (Maggie); Dalena R.M. Van Rooyen; Esmeralda J. Ricks (AOSIS, 2016)
Despite efforts to scale up access to antiretroviral therapy (ART), particularly at primary health care (PHC) facilities, antiretroviral therapy (ART) continues to be out of reach formany human immunodeficiency virus (HIV)-positive children in sub-Saharan Africa. In resource limited settings decentralisation of ART is required to scale up access to essential medication. Traditionally, paediatric HIV care has been provided in tertiary care facilities which have better human and material resources, but limited accessibility in terms of distance for caregivers of HIV-positive children. The focus of this article is on the experiences of caregivers whilst accessing ART for HIV-positive children at PHC (decentralised care) facilities in Nelson Mandela Bay (NMB) in the Eastern Cape, South Africa. A qualitative, explorative, descriptive and contextual research design was used. The target population comprised caregivers of HIV-positive children. Data were collected by means of indepth individual interviews, which were thematically analysed. Guba's model was usedto ensure trustworthiness. Barriers to accessing ART at PHC clinics for HIV-positive children included personal issues, negative experiences, lack of support and finance, stigma and discrimination. The researchers recommend standardised programmes be developed and implemented in PHC clinics to assist in providing treatment, care and support for HIV positive children.